Oral health quality of life in children with cerebral palsy : parental perception - Ishak, Ahmed Mostafa Kamel (My University, 2019)
Amaç: Bu çalışmada Serepral Palsi (SP) hastalarının ağız sağlığını, ağız sağlığı ile ilgili yaşam kalitesini ve ebeveynlerinin algılarını sağlıklı çocuklarla karşılaştırarak araştırılması hedeflendi.Gereç ve Yöntem: Çalışma grubu Marmara Üniversitesi Tıp Fakültesi Fizik Tedavi ve Rehabilitasyon bölümüne başvurmuş olan 4-14 yaş grubundaki 50 çocuk hastadan oluştu. Aynı yaş ve cinsiyetten 50 sağlıklı okul çocuğu kontrol grubu olarak belirlendi. Çürük, eksik, dolgulu diş sayısı (dmft/ DMFT) basitleştirilmiş ağız hijyeni indeksi (OHI-S), modifiye diş eti indeksi (MGI) değerlendirildi. Çocukların ebeveynleri Türkçe Pediatrik Ağız Sağlığında Yaşam Kalitesi (POQL) Ölçeğini doldurdu.Bulgular: POQL değeri ortalaması; SP grubunda 14.06, kontrol grubunda 6.44, SP hastaların POQL, OHI-S, MGI değerleri daha yüksek bulunmuştur. İstatistiksel farklılık POQL, OHI-S, MGI skorlarında ortaya çıktı. (P<0.05). SP grubunda DMFT ve dmft skorları açısından kontrol grupla benzer sonuçlar saptandı. Ayrıca, SP ve kontrol grubunda diş çürüğünün şiddeti ve gingival enflamasyon, ağız sağlığı ile ilgili yaşam kalitesi üzerinde olumsuz bir etkiye sahiptir (P<0.05).Sonuç: SP hastalarının ağız sağlığı ile ilgili yaşam kalitesi, oral hijyeni ve gingival sağlık durumu sağlıklı kontrol grubuna göre daha kötü seviyededir. SP hastalarının yaşam kalitesini artırmak için koruyucu tedaviler planlanmalıdır. Çocuk doctor, pedodontist ve aileler çocuğun ağız hijyeni alışkanlıklarını kazandırmak için çaba gösterilmelidir

Aim: The aim of this study was to evaluate and compare the oral health status and oral health related quality of life (OHRQOL) of children with cerebral palsy (CP) with healthy children in Istanbul, Turkey.Material and Methods: 50 children with CP (19 females and 31 males) from Department of Physical Medicine and Rehabilitation, School of Medicine, Marmara University, and age and sex-matched 50 healthy children from government schools were examined. An oral examination was carried out and decayed, missing, and filled teeth (dmft/ DMFT) , oral hygiene index-simplified (OHI-S) index, modified gingival index (MGI) were charted and Turkish version of pediatric oral health-related quality of life survey (POQL) was completed by the parents.Results: The mean POQL of the CP group was 14.06, while that of controls was 6.44, this difference was statistically significant (P=0.008). The examination showed also higher OHI-S and MGI scores in the CP group (P=0.003, P=0.03 respectively). No statistically significant difference was found between CP and healthy children in terms of caries experience in primary dentition (dmft) or in permanent dentition (DMFT) (P=0.18, P=0.24 respectively). Caries experience and gingival inflammation were conditions strongly associated with a negative impact on OHRQOL of children in both groups (P<0.05). Conclusions: The OHRQOL, gingival health and the level of oral hygiene of children with CP is significantly lower than that of healthy children. Effort of the physician, the family and the pediatric dentist should combine to provide good oral care and deliver preventive methods for CP children which can help to improve their quality of life.
Keywords: Ağız sağlığı; Ağiz sağliği ile ilgili yaşam kalitesi; Çocuk Diş Hekimliği; OHRQOL; Oral health; Pediatric Dentistry; POQL Cerebral palsy; Quality of life; Serebral palsi